Situation Report: Poland, 9 November 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Further Limitations on Civil Rights A Jittery Time in Poland Waldemar Swirgon Appointed CC Secretary Glemp-Jaruzelski Meeting: Pope to Poland Next June Olszowski in East Berlin Sundry Items